Semantic and Pragmatic Potential of Adverb po-kitayski ‘in Chinese’ in Modern Russian Media - O. A. Mikhaylova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The research is carried out in the context of pragmalinguistics and is devoted to the question of means of forming stereotypes in the texts of journalistic discourse. The semantics and pragmatics of the lexeme po-kitayski ‘in Chinese’ as a diagnostic language means manifesting collective stereotypical ideas about China are considered. The material for the study is the statements extracted from the modern Russian media in the electronic database Integrum. Texts about policy, state economy, Chinese cuisine and New year’s holiday in China are presented. It is shown that the analyzed adverb is used in verbal and substantive word combinations with concrete and abstract nouns. The material indicates that verbal phrases characterize specific processes occurring in China. The thesis that substantial-adverbial word combinations are used to characterize or reinterpret known concepts is put forward. The article presents the results of the analysis of the contextual semantics of the adverb po-kitayski , which is complicated by the background features that actualize a number of typical characteristics of the Eastern state (a specific form of globalization, a special socialist model, the task of eradicating corruption at all levels, economic breakthrough, preservation of cultural traditions). In the Russian media there is an estimated duality in the representation of China. Stereotypes about China are mostly positive: a prosperous economy, political independence, ancient traditions. In particular, the low quality of goods produced in China and the cruelty of political measures receive a negative assessment.